2018
DOI: 10.3897/zookeys.751.20541
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Pristimantis (Anura, Craugastoridae) from the Cajas Massif, southern Ecuador

Abstract: A new species of Pristimantis is described from the highland paramos on the eastern slopes of the Cajas Massif, southern Andes of Ecuador, at 3400 m. This new species is characterized by having a distinctive reddish color, cutaneous macroglands in suprascapular region and surfaces of arm and legs, and by lacking dentigerous processes of vomers. The cutaneous macroglands are similar to those exhibited by several species of the Pristimantis orcesi group, and may suggest a close phylogenetic relationship. The new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
4
0
2
Order By: Relevance
“…Pristimantisandinogigas shows two notorious morphological characters that are not extended in the genus: glandular patches covering dorsal surfaces body and limbs, and porous dorsal skin texture. Similar glandular patches were first reported in P. pycnodermis by Lynch (1979), subsequently in P.loujosti by Yánez-Muñoz et al (2010) and in P.erythros by Sánchez-Nivicela et al (2018), and we have observed them in P.orcesi and an undescribed species of Pristimantis from the paramos of southern Ecuador. Porous skin texture has not been reported in any other species of Pristimantis , although it could have been confused with shagreen texture when not examined in detail or in preserved specimens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pristimantisandinogigas shows two notorious morphological characters that are not extended in the genus: glandular patches covering dorsal surfaces body and limbs, and porous dorsal skin texture. Similar glandular patches were first reported in P. pycnodermis by Lynch (1979), subsequently in P.loujosti by Yánez-Muñoz et al (2010) and in P.erythros by Sánchez-Nivicela et al (2018), and we have observed them in P.orcesi and an undescribed species of Pristimantis from the paramos of southern Ecuador. Porous skin texture has not been reported in any other species of Pristimantis , although it could have been confused with shagreen texture when not examined in detail or in preserved specimens.…”
Section: Discussionsupporting
confidence: 90%
“…Ecuador holds 39% of all Pristimantis species (210 spp., Ron et al 2019), but its diversity is still underestimated, and 61 species have been discovered and scientifically described in the country during the last decade (Ron et al 2019). Pristimantis from the Andes of southern Ecuador are little known; with new species frequently discovered, new distributional records revealed, collections of putatively new species deposited in museum collections, and several areas unexplored (Bustamante and Mendelson III 2008, Cisneros-Heredia et al 2009, Reyes-Puig et al 2010, 2010, 2014, 2015, Yánez-Muñoz et al 2010, 2010, 2010, 2012, 2016, 2016, 2016, Camacho-Badani et al 2012, Reyes-Puig and Yánez-Muñoz 2012, Brito and Pozo-Zamora 2013, Urgilés et al 2014, 2014, 2014, Brito et al 2017, Urgiles et al 2017, Sánchez-Nivicela et al 2018, Reyes-Puig et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The regions with the most homogeneous topography (Amazon Basin) present a high number of species that undergo a process called morphological stasis [16], where species that suffer strong selection by the environment or physiological characters for adaptation in a specific habitat, may not present morphological changes between species [63]. This morphological conservatism in Pristimantis represents one of the main problems for accurate identification of the species, resulting in an underestimated number of species for this genus [64], [65].…”
Section: Discussionmentioning
confidence: 99%
“…La distribución restringida de P. andinodiabolus en el bosque montano de la microcuenca del río Llavircay coincide con lo observado en P. erythros, cuya distribución también se encuentra restringida a un pequeño parche de matorrales en el páramo de Chanlud, en Azuay [10]. Las distribuciones de ambas especies demuestran la importancia de conservar y proteger esta área, sobre todo al develarse los microendemismos que presenta.…”
Section: Discussionunclassified
“…Recientemente, dos nuevas especies descritas de los páramos del sur del Ecuador: P. erythros [10] y P. andinogigas [11], han sido tentativamente sugeridas como miembros del grupo P. orcesi debido a sus similitudes morfológicas con P. orcesi, incluyendo la presencia de macroglándulas dermales. Las macroglándulas son un carácter poco común en el género Pristimantis y hasta ahora solamente han sido reportadas en las especies mencionadas y P. pycnodermis, P. orcesi y P. loujosti [10,12]. Sin embargo, las relaciones evolutivas entre estas especies de ranas glandulares son aún inciertas porque, hasta la fecha, no habían secuencias que permita incluirlas en análisis filogenéticos.…”
Section: Introductionunclassified